2020
DOI: 10.1177/0300060520903868
|View full text |Cite
|
Sign up to set email alerts
|

Salusin-β is superior to salusin-α as a marker for evaluating coronary atherosclerosis

Abstract: Objective: This study was performed to evaluate the interaction effect of salusin-a and salusin-b on coronary artery injury or stenosis. Methods: The salusin-a and salusin-b concentrations were measured by enzyme-linked immunosorbent assay in 256 patients who underwent coronary angiography for chest pain, and coronary artery stenosis was assessed by the SYNTAX scoring system. Multivariate logistic regression was used to analyze the correlation between variables and coronary artery stenosis. The interaction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Also, in agreement with our results, Gao, et al indicated that salusin-α decreased MMP-2/-9 expression in aortic plaque and VSMCs and subsequently repress the development of atherosclerosis by prevention the VSMC proliferation and migration (32). MMPs have major role in stenosis, Wang et al reported the association of salusins serum level with coronary artery stenosis (33) In addition, our previous studies indicated that salusin-α decreases and salusin-β increases in ammatory interleukines(IL) -6, -8 and − 18 (mRNA and protein level) in HUVECs (21,22). IL-8 could suppress expression of TIMP-1 (34) and increases mRNA/ protein of MMP-2 and MMP-9 in endothelial cells (35).…”
Section: Discussionmentioning
confidence: 96%
“…Also, in agreement with our results, Gao, et al indicated that salusin-α decreased MMP-2/-9 expression in aortic plaque and VSMCs and subsequently repress the development of atherosclerosis by prevention the VSMC proliferation and migration (32). MMPs have major role in stenosis, Wang et al reported the association of salusins serum level with coronary artery stenosis (33) In addition, our previous studies indicated that salusin-α decreases and salusin-β increases in ammatory interleukines(IL) -6, -8 and − 18 (mRNA and protein level) in HUVECs (21,22). IL-8 could suppress expression of TIMP-1 (34) and increases mRNA/ protein of MMP-2 and MMP-9 in endothelial cells (35).…”
Section: Discussionmentioning
confidence: 96%
“…Salusin-β is a bioactive peptide that is involved in certain cardiovascular diseases and has been previously associated with abnormal lipid metabolism (16). A previous clinical study reported that serum salusin-β levels are positively associated with TG levels and the TG/HDL ratio in children and adolescents with hypertension (17).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of the multiple linear regression model through analysis of variance revealed F > F 0.05 , p < 0.05, and R 2 > 0.9; these findings indicated that the practical design equation had high reliability. [15][16][17] The design equation showed that, among the factors influencing Q IF-Max , L/D had a much greater impact on convection effects, compared with N/D 2 . Therefore, L/D optimization can significantly increase Q IF-Max and enhance convection effects, thus improving the MM removal performances of CRRT filters.…”
Section: A Practical Design Equation To Quantify Design Factors and C...mentioning
confidence: 99%